Progression in patients with low- and intermediate1-risk del(5q) myelodysplastic syndromes is predicted by a limited subset of mutations. - Scharenberg, C; Giai, V; Pellagatti, A; Saft, L; Dimitriou, M; Jansson, M; Jädersten, M; Grandien, A; Douagi, I; Neuberg, D; LeBlanc, K; Boultwood, J; et al. (Ferrata Storti Foundation, 2016)
A high proportion of patients with lower-risk del(5q) myelodysplastic syndromes (MDS) will respond to treatment with lenalidomide. Median duration of transfusion-independence is 2 years with some long-lasting responses, but almost 40% of patients progress to acute leukemia by 5 years after start of treatment. Mechanisms underlying disease progression other than the well-established finding of small TP53-mutated subclones at diagnosis remain unclear. We studied a longitudinal cohort of 35 low- and intermediate-1-risk del(5q) patients treated with lenalidomide (n=22) or not (n=13) by flow cytometric surveillance of hematopoietic stem and progenitor cells (HSPC) subsets, targeted sequencing of mutational patterns, and changes in the bone marrow microenvironment. All 13 patients with disease progression were identified by a limited number of mutations in TP53, RUNX1, and TET2, respectively, with PTPN11 and SF3B1 occurring in one patient each. TP53 mutations were found in 7 of 9 patients who developed acute leukemia, and were documented to be present in the earliest sample (n=1) and acquired during lenalidomide treatment (n=6). By contrast, analysis of the microenvironment, and of HSPC by flow cytometry was of limited prognostic value. Based on our data, we advocate conducting a prospective study aimed at investigating, in a larger number of del(5q) MDS cases pre- and post-lenalidomide treatment, whether the detection of such mutations can guide clinical decision making.